SYSTEMATIK LITERATURE REVIEW PENGEMBANGAN POTENSI BRANDING UMKM MELALUI PROSES DIGITALISASI BISNIS - Lubis, Siti Sahara; Veri, Jhon (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
In the current era, micro small and Medium Enterprises must use digital platforms as a marketing strategy for their products so that consumers can become more familiar with the products they produce. Service activities with the theme of Developing micro small and Medium Enterprises Branding Potential through the business digitalization process. A systematic literature review (SLR) is a secondary study to map, identify, critically express, consolidate, and collect the results of primary studies on a particular research topic. From 2,810 data, ± 50 journals were obtained which were almost similar to the research theme which would enter the screening stage using inclusion and exclusion criteria to ensure the quality and relevance of the articles to the themes raised. The results of this Community Service activity suggest that Service Partners continue use of digital marketing strategies and receive regular guidance. This aims to ensure the effectiveness and optimality of this strategy in supporting micro small and Medium Enterprises marketing and increasing the sales turnover of MSME businesses in the future.